The comparison of causal relationships of job stress between Thai immigrant employees with and without rearing their aging parents - Chonticha Kaewanuchit; Yothin Sawangdee (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The occupational stress is a disadvantage resulting in mental health illnesses that have been found when looking at those migrants who were young adults and migrated to work in the urban areas, leaving behind their aging parents to live alone at home. The purpose of this paper is to compare the causal relationships of job stress between Thai immigrant employees with and without rearing aging parents. Design/methodology/approach - The research was a cross-sectional survey. The sample for this study included 600 Thai immigrant employees (300 cases per group) in 2016. Measures included individual characteristics, working conditions, and a Thai Job Content Questionnaire (Thai-JCQ) on related job stress. The model was verified using a path model by Mplus software. Findings - The distance traveled between the house and the workplace, wages, working conditions had a direct effect on job stress. Working conditions among Thai immigrants employees with rearing aging parents had the most direct effect on job stress with a standardized regression weight of 0.552 (p-value <0.05) as well as working conditions among their without rearing aging parents had the most direct effect on job stress with a standardized regression weight of −0.292. Originality/value - This research demonstrated that working conditions were an important factor.